Quintais agroecológicos: sala de aula informal paracapacitação formal - as experiências do assentamento rural Araras 4 - Mantovanelli, Diogo Fonseca (2012)
Given that the extinction of biodiversity, and considerable environmental and social degradation, is intrinsically linked to the conventional mode of production and consumption patterns, it becomes possible to identify that the challenge we face is not simply a matter of achieving the global demand for food since, quantitatively, this objective has been reached. Science is then faced with a paradigm. It is crucial that scientists involved in the search for environmentally friendly and sustainable agricultural technologies worry about who actually will be benefited from them. It is also necessary to identify what is produced, how it is produced and for whom it is produced. Accordingly, agroecological production systems shows to be responsible for the recovery of soil fertility, promotion of food sovereignty and social inclusion of individuals affected by it. In the same way, permaculture design proposes the systemic thought and conception of ecological principles so the planning, the management and the improvement of the efforts made by individuals and communities may lead to a viable future. These two approaches provide technical and practical subsidies for sustainable use of natural resources and should be included in actions of technical assistance and rural extension (ATER acronym in portuguese). The purpose of this work was to systematize the experiences of an action research in critical ATER, which resulted in the training of agroecology and permaculture students from UFSCar and producers of the settlement Araras 4, located in the municipality of Araras, São Paulo, Brazil. Based on the results, we can conclude that the teaching of agroecology and permaculture, practical experience and educational spaces can assist in teaching and learning, and provides products and models to be followed by producers.